Negotiating Women’s Agency in Marriage Choice: A Case Study of Muslim Society in Kerinci - Purwanto, Jepri; Yul, Widiya; Afridawati, Afridawati; Efyanti, Yasni; Rahmatullah, Prayudi (Al-Qisthu, 2024)
Arranged marriages remain significant in Muslim Kerinci society, where cultural traditions and Islamic values shape family life. This study explores the factors sustaining marital harmony and how women negotiate agency within family expectations and religious norms. Using a qualitative approach with in-depth interviews involving community leaders, scholars, and couples in Air Hangat Barat District, the research highlights the interplay between structural norms and individual choices. Findings show that shared religious values, moderation in household management, tolerance of shortcomings, supportive parental roles, and affection rooted in Islamic teachings are key to harmonious families. While cultural and religious frameworks function as structural constraints, women exercise agency by negotiating their roles and influencing marital outcomes. The study’s novelty lies in integrating Islamic perspectives with sociological and gender theories to explain how tradition, faith, and agency interact to sustain arranged marriages in contemporary Muslim contexts.